2010
DOI: 10.1111/j.1467-8659.2010.01714.x
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Use of Non‐Terminal Symbols for Procedural Modeling

Abstract: We present the new procedural modeling language G 2 (Generalized Grammar), which adapts various concepts from general purpose programming languages to provide high descriptive power with well-defined semantics and a simple syntax which is easily readable even by non-programmers. The term 'Generalized' reflects two kinds of generalization. On the one hand, we extend the scope of previous architectural modeling languages by allowing for multiple types of non-terminal objects with domain-specific operators and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 26 publications
0
43
0
1
Order By: Relevance
“…• rule-based: using substitutions and substitution rules to generate complex structures out of simple starting structures [29][30][31][32]; • imperative and scripting-based: using a scripting engine and techniques from predominant programming languages [20,33,34] or; • GUI and dataflow-based: using new graphical user interfaces (GUI) and intelligent GUIs to detect structures in modeling tasks, which can be mapped onto formal descriptions [35,36].…”
Section: Language Processing and Compiler Constructionmentioning
confidence: 99%
“…• rule-based: using substitutions and substitution rules to generate complex structures out of simple starting structures [29][30][31][32]; • imperative and scripting-based: using a scripting engine and techniques from predominant programming languages [20,33,34] or; • GUI and dataflow-based: using new graphical user interfaces (GUI) and intelligent GUIs to detect structures in modeling tasks, which can be mapped onto formal descriptions [35,36].…”
Section: Language Processing and Compiler Constructionmentioning
confidence: 99%
“…• rule-based: using substitutions and substitution rules to generate complex structures out of simple starting structures (Özkar and Kotsopoulos, 2008), (Krecklau et al, 2010), (Müller et al, 2006c), (Snyder and Kajiya, 1992).…”
Section: Language Processing and Compiler Constructionmentioning
confidence: 99%
“…[Wonka et al 2003] and entire buildings. The most prominent example is CGA shape [Müller et al 2006], for which also extensions [Krecklau and Kobbelt 2011;Whiting et al 2009] and generalizations, like enhanced language expressiveness [Krecklau et al 2010], were suggested. Motivated by its wide use, we chose the recent variant of CGA shape found within the commercial software CityEngine [Esri 2012] as basis for our system's grammar language.…”
Section: Related Workmentioning
confidence: 99%